STRATEGI MINDSET ENGLISH CENTER PAREPARE PERSPEKTIF MANAJEMEN SYARIAH - Rubiah; Moh. Yasin Soumena; Abdul Hamid (Institut Agama Islam Negeri Parepare, 2020)
This research is a qualitative research using a sociological normative approach. Data were collected using observation and interview methods. Data analysis technique used is to reduce data, present data and draw conclusions. The results of this study can be stated that 1) Strategic planning of the Parepare English Center Mindset can help, assist and ease the cost of English courses. 2) Implementation of the Parepare Mind Center English Center strategy, which means that participants can make payments easier. 3) Evaluate the Parepare Mind Center English Center strategy to run effectively and efficiently. If this is related to sharia management, it is in accordance with the principles of sharia management, namely justice, trustworthiness and accountability, as well as communicative.